Ocupación por arboles de calidad: un concepto para evaluar plantaciones - Rodríguez Arellano, María Martha; Mendoza Briseño, Martín Alfonso; Avila Bello, Carlos Héctor; Pacheco Velazco, José Evaristo (Instituto de Ecología, A.C., 2016)
The quality tree occupancy concept is presented as a basis for evaluation of plantations. This concept joins the null plot idea with a vitality rating that goes from a dead tree to an excellent tree. Quality frequencies are then fitted to explanatory variables that represent environment, and tree development patterns. A sample of tropical plantations from Los Tuxtlas, Veracruz, Mexico, serves as an example illustrating the concept’s capability to depict quantitatively a plantation condition. The model fitted to the Tuxtlas example demonstrated that it is possible to infer a biological interpretation of current conditions, estimate a prognosis of further development, and suggest prescriptions to correct trends, should the need arose.